Kinetics and mechanism of Prussian blue formation - R.K. Adhikamsetty (Bulletin of the Chemical Society of Ethiopia, 2009)
The kinetics of reaction between ferrocyanide and ferric ions under acidic conditions was studied at fixed ionic strength (0.1 M) and (25 plus or minus 0.1) oC by using the stopped flow technique, under limiting conditions of [ferrocyanide] and with other reactants in excess. The reaction had first-order dependence on ferrocyanide, Fe(III) and H+ ion concentrations and had negative salt effect. On the basis of the experimental findings, a plausible mechanism for the formation of soluble form of Prussian blue (KFe{Fe(CN)6}x H2O) and rate law are proposed. The activation parameters for the title reaction are estimated. A relatively low energy of activation (23 kJ mol-1) and high negative entropy of activation (-231 J K-1 mol-1) agree well with the proposed mechanism and configuration of complex ion leading to the formation of insoluble Prussian blue, Fe4{Fe(CN)6}3 y H2O.